Dietary habits of type 2 Diabetes patients: frequency and diversity of nutrition intake – Kingdom of Saudi Arabia - Sami, Waqas; Alabdulwahhab , Khalid M; Ab Hamid, Mohd Rashid; Alasbali, Tariq A; Alwadani , Fahd Al; Ahmad, Mohammad Shakil (Progress in Nutrition, 2020)
One of the important cornerstones of diabetes care is dietary management which should be based on healthy eating in context of food choices, cultural and social aspects. There is scarcity of literature adressing the dietary habits of type 2 diabetics in the Kingdom of Saudi Arabia (KSA). In Gulf countries, especially KSA there are ineffective dietary habits programs that can prevent and control complications from diet-related non-communicable diseases like diabetes  The present study was conducted to examine the dietary habits and food frequencies of type 2 diabetes patients attending the primary healthcare centers in Almajmaah City, KSA. It was an analytical cross-sectional study by design which was conducted from February – April 2017. A self-prepared Food Frequency Questionnaire (FFQ) in English language was used to collect the data from 350 patients. The FFQ comprised of local food items that were distributed in 9 food groups. The selection of patients was done by means of systematic random sampling technique. The median age of the patients was 45 years. When compared with the food guide pyramid, the consumption of lipids and fats, sweets and bakery, drinks and, soups and sauces were more than the recommended intake (p